VULNERABILITY AND RESPONSE TO COVID-19 IN WEST AFRICA - KEDOTE, Nonvignon Marius; SOSSA-JEROME, Charles; WEWE, Binet (MEDECINE LEGALE DROIT MEDICAL, 2025)
The response measures adopted to control the COVID-19 epidemic may have had a devastating impact on the most vulnerable populations. The objective of this paper was to analyze the vulnerability of certain population groups to the response to COVID-19 in West Africa. Among the preventive measures implemented in West African countries were strict confinement in some of their megacities, the cordoning off of cities or regions with free movement of people and goods, the closure of public places including schools, and vaccination campaigns against COVID-19. These different response measures have further contributed to the increase in inequalities and a deterioration in the socio-economic resilience of the most vulnerable and weakest groups in society. The lack of social safety nets has contributed to the increased precariousness of workers in the informal sector. Gender issues and inequalities in access to education have been exacerbated. For future response strategies to epidemics of the same magnitude need to include measures that take into account the realities of vulnerability and help ensure social and economic stability for all groups in society.